Association of the VACS Index With Hospitalization Among People With HIV in the NA-ACCORD. (1st January 2022) - Qian, Yuhang; Moore, Richard D.; Coburn, Sally B.; Davy-Mendez, Thibaut; Akgün, Kathleen M.; McGinnis, Kathleen A.; Silverberg, Michael J.; Colasanti, Jonathan A.; Cachay, Edward R.; Horberg, Michael A.; Rabkin, Charles S.; Jacobson, Jeffrey M.; et al.
Abstract : Background: People with HIV (PWH) have a higher hospitalization rate than the general population. The Veterans Aging Cohort Study (VACS) Index at study entry well predicts hospitalization in PWH, but it is unknown if the time-updated parameter improves hospitalization prediction. We assessed the association of parameterizations of the VACS Index 2.0 with the 5-year risk of hospitalization. Setting: PWH ≥30 years old with at least 12 months of antiretroviral therapy (ART) use and contributing hospitalization data from 2000 to 2016 in North American AIDS Cohort Collaboration on Research and Design (NA-ACCORD) were included. Three parameterizations of the VACS Index 2.0 were assessed and categorized by quartile: (1) "baseline" measurement at study entry; (2) time-updated measurements; and (3) cumulative scores calculated using the trapezoidal rule. Methods: Discrete-time proportional hazard models estimated the crude and adjusted associations (and 95% confidence intervals [CIs]) of the VACS Index parameterizations and all-cause hospitalizations. The Akaike information criterion (AIC) assessed the model fit with each of the VACS Index parameters. Results: Among 7289 patients, 1537 were hospitalized. Time-updated VACS Index fitted hospitalization best with a more distinct dose–response relationship [score <43: reference; score 43–55: aHR = 1.93 (95% CI: 1.66 to 2.23); score 55–68: aHR = 3.63 (95% CI: 3.12 to 4.23); score ≥68: aHR = 9.98 (95% CI: 8.52 to 11.69)] than study entry and cumulative VACS Index after adjusting for known risk factors. Conclusions: Time-updated VACS Index 2.0 had the strongest association with hospitalization and best fit to the data. Health care providers should consider using it when assessing hospitalization risk among PWH. Abstract : Supplemental Digital Content is Available in the Text.